Non-Iterative Technique for Determination of Full Lightning Impulse Voltage Parameters - Peerawut Yutthagowith (Energies, 2022)
This paper introduces an effective and non-iterative technique for the determination of full lightning impulse voltage parameters in high-voltage tests. In the waveform parameter determination, the base curve parameters are determined on the basis of precomputed models that are utilized to correct the base curve parameters. Using the data from the cases collected from the standard, the correction factors are computed from the deviation of the parameters which are determined by the proposed and standard recommended method. With the accurate base curve parameters, the waveform parameters can be calculated precisely. Because there is no iterative process in the technique, the proposed method has a simplified computational algorithm and becomes an attractive method.
Keywords: Lightning and Electromagnetic Phenomena; Power Transformer Diagnostics and Insulation; Power Quality and Harmonics